IMPLEMENTASI KEBIJAKAN KARTU LANSIA JAKARTA DI KELURAHAN PONDOK LABU JAKARTA SELATAN - Irene Yustika Lintin, (2022)
This research aims to analyze the implementation of the Jakarta Elderly Card (Kartu Lansia Jakarta/KLJ) policy which is the policy of DKI Jakarta Province Government under Anies Baswedan Governor leadership, focused on the implementation in Pondok Labu Urban-Village, South Jakatya that includes 11 recipients in 2021. This research used public policy implementation theory by Merilee S. Grindle, social policy concept, and elderly concept. This research also used a qualitative approach that aims to describe and explore the research. Meanwhile, data collection techniques rely on primary data through interviews and secondary data through documentation study. According to the result of the research, Jakarta Elderly Card (Kartu Lansia Jakarta/KLJ) has fulfilled the basic needs of elderly in Pondok Labu economically and physically. But several obstacles resulted in the least number of recipients and the delay of disbursement of funds, which are lack of political will from the national government in distributing funds in time, implementor in Pondok Labu Urban-Village that did not deepen and not having strategic visions, and missions in implementing Jakarta Elderly Card (Kartu Lansia Jakarta/KLJ), and limited budget, because the funds prepared, are not in proportion to the number of needed elderly in Jakarta.